PENERAPAN LATIHAN DASAR PERCUSSION LINE PADA MARCHING BAND SEMEN PADANG - Ramadanel, Zulgian; Hadi, Harisnal (Universitas Negeri Padang, 2026)
This study aims to describe the implementation of basic percussion line training in the Semen Padang Marching Band using a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing. The results show that training begins with physical and technical warm-ups. Technical warm-ups include loosening the finger and wrist muscles without and with sticks/mallets, grip technique, basic strokes (natural stroke and downstroke), basic percussion rudiments, dynamics, legato, and staccato. The up stroke is not taught because it is considered difficult and time-consuming. Rudiments for PIT instruments include single stroke, double stroke, and accent tap, while battery percussion uses single stroke, double stroke/diddles, roll, accent tap, and flam. All techniques are tailored to support the repertoire performed for the 2025 Parade Senja.